GANTI RUGI BANGUNAN YANG DIDIRIKAN DIATAS TANAH SEWA MILIK PIHAK LAIN (STUDI PUTUSAN MAHKAMAH AGUNG NO.534/K/PDT/2016) - Vitiamawan, Renaldo; Pandamdari, Endang (Jurnal Hukum Adigama, 2020)
In article 50 rule No. 1 of 2011 concerning building and Settlements reside or occupy the house while the right to inhabit the house can be: ownership or rent or not by way of rent, an agreement is an event wherein person promised for someone else or wherein the deuce people promised each other to carry out one thing. With such provisions it raises legal issues about how the compensation for buildings erected on land owned by another party (study of court decision angung No.534 / K / PDT / 2016)? Referring to that problem, the writer uses the actually everyone has the right to live or occupy the house, while the right to occupy the house can be: ownership or lease or not by leasing. However, an agreement must be made first based on statutory regulations, where the agreement made by verbally, in the case that the evidence must be witnessed by at least 2 people and the defendant cannot prove the truth of the rental agreement made verbally. thus it can be concluded that if you want to build a erect buildings on land not his, an agreement must be made first. The author suggests, if building a erect buildings on land not his, an agreement must be made first and it is better if the agreement is made in writing so that if problems occur, it can be used to defend the rights owned.